2009
DOI: 10.1038/gene.2008.100
|View full text |Cite
|
Sign up to set email alerts
|

A TLR2 polymorphism is associated with type 1 diabetes and allergic asthma

Abstract: Type 1 diabetes (T1D) and allergic asthma are immune-mediated diseases. Pattern recognition receptors are proteins expressed by cells in the immune system to identify microbial pathogens and endogenous ligands. Toll-like receptors (TLRs) and CD14 are members of this family and could represent a molecular link between microbial infections and immune-mediated diseases. Diverging hypotheses regarding whether there exists a common or inverse genetic etiology behind these immunemediated diseases have been presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…Gene polymorphisms in TLRs affect the innate immune response [25]. Previous studies have recognized that polymorphisms in TLRs are associated with the development of diabetes [14,26,27,28,29,30,31,32,33,34,35,36]. Table 5 shows polymorphisms previously associated with diabetes and references.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene polymorphisms in TLRs affect the innate immune response [25]. Previous studies have recognized that polymorphisms in TLRs are associated with the development of diabetes [14,26,27,28,29,30,31,32,33,34,35,36]. Table 5 shows polymorphisms previously associated with diabetes and references.…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 shows polymorphisms previously associated with diabetes and references. Bjørnvold et al [28] reported that the TLR2 rs3804100 SNP is associated with T1DM. However, our data did not show a significant association between TLR2 SNPs and PTDM.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of TLR1, TLR6 and TLR10 (these receptors can form heterodimers with TLR2) were reported to exert a protective effect against asthma [27]. Several studies have identified significant associations between TLR2 polymorphisms and increased risk of asthma [27,28,34], whereas polymorphisms of TLR3 were not associated with asthma [27]. Infectious agents potentially interact with other environmental factors such as family size, country versus city living, attendance at day care centres, schools and so on to influence the development of asthma.…”
Section: Genetics and The Host Response To Infection: Implications Fomentioning
confidence: 94%
“…The common genetic risks for bronchiolitis and asthma have recently been reviewed (Bartlett et al, 2009). These genes include those involved in the innate/Th1 response to infection [e.g., Toll-like receptors and CD14 (Hong et al, 2007;Kormann et al, 2008;Bjornvold et al, 2009)], and those encoding for interferons [e.g., interferon-γ gene (Kumar and Ghosh, 2008), interferon regulatory factor-1 gene (Schedel et al, 2008)], as well as the interleukin-13 and interleukin-14 genes (Forton et al, 2009). The sequence variant rs7216389 in ORMDL3 was shown to be associated with the risk of childhood asthma in a genome-wide association study of asthma (Moffatt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%